(untitled) (diségno, 2021)
The Engineering Department of the University of Palermo organized and hosted the fourth edition of the itinerant study day Documentation & Digital [1]. The event, promoted by the Italian Union for Drawing, held in mixed mode on 20 September 2021 in the Steri Monumental Complex. [read more]